Integrating community health workers into HIV care clinics: a qualitative study with health system leaders and clinicians in the Southern United States - Shannon M. Fuller; Emily A. Arnold; Jessica Xavier; Chidinma A. Ibe; Wayne T. Steward; Janet J. Myers; Greg Rebchook; Kimberly A. Koester (BMC, 2024)
Abstract Background Community health workers (CHWs) can support patient engagement in care for a variety of health conditions, including HIV. This paper reports on the experiences of HIV clinics and health departments that integrated CHWs into their health systems as part of a capacity-building initiative to address HIV-related disparities in the United States. Methods Semi-structured interviews were conducted with key informants (n = 14) in two Ryan White HIV/AIDS program jurisdictions: Mississippi (jurisdiction covers the entire state) and the city of New Orleans, Louisiana. This work was part of a larger evaluation of an initiative that used a Learning Collaborative model to facilitate the implementation of evidence-informed interventions to address HIV care continuum gaps in four jurisdictions. The two jurisdictions that focused on integrating CHWs into HIV care clinics and support service agencies were selected for this sub-analysis. Interview participants included HIV clinic leaders and staff, health department leaders, and other Learning Collaborative leaders. Interview transcripts were coded and analyzed for themes related to the acceptability, feasibility, and perceived impact of CHW integration. Results Overall, participants expressed interest in having support from CHWs at HIV clinics and service agencies to assist with patient retention and engagement efforts. However, there were challenges integrating CHWs into existing systems (e.g., gaining access to electronic health records, changing policies to conduct home visits, and clarifying roles and scope of work). Negotiating contracts and accessing funding for CHW positions presented major challenges that often contributed to turnover and conflicts around scope of practice. When health departments leveraged existing funding streams to support CHW positions, the clinics and agencies where the CHWs worked had limited flexibility over the hiring process. Conclusions Our findings reinforce the value and acceptability of CHWs as part of the workforce in HIV clinical and support service settings; however, integrating CHWs into clinics and service agencies required effort. Training the CHWs was not sufficient; other staff and clinicians had to understand the role of CHWs to facilitate their integration into health systems. Resources are needed to support organizations in incorporating CHWs effectively, and long-term, flexible sources of funding are necessary for these positions.